Formula Optimization of Black Mulberry and Canistel Mixed Juice using Mixture D-Optimal from Design Expert Software - Yusuf Irfan; Yusman Taufik; Nana Sutisna Achyadi (Food Science and Technology Journal (Foodscitech), 2022)
Black mulberry (Morus nigra L.) and canistel (Pouteria campechiana) are classified as fruit commodities that are still not optimal in their utilization. Based on their sensory and nutritional characteristics, they have potential to be processed into products for a longer shelf life and more valuable. The purpose of this study was to determine the optimal formula for a mixed fruit juice product made from black mulberry and canistel in terms of chemical, physical and sensory characteristics. The optimization formula was analyzed by Design Expert software ver.11 and through the Mixture D-Optimal method. The independent variables in this study are black mulberry puree, canistel puree, and sucrose. The dependent variables were 0.05% sodium benzoate and a mixture of CMC and sodium alginate 0.25% with a ratio of CMC: sodium alginate 1:1. The chemical parameters analyzed consisted of anthocyanin, beta carotene, vitamin C, and antioxidant activity. The physical parameters consisted of viscosity and sensory parameters consisted of flavor, sweet taste, and sour taste. The results obtained that the optimal formulation was based on the highest desirability value from the results of the analysis using the Design Expert program and the value was 0.807. The optimal formula for mixed fruit juices was black mulberry puree 53.356%, canistel puree 35.252%, and sucrose 11.092%.